POSSIBLE TEMPORARY PARAMETERS IN THE CENTRALIZED STRUCTURE OF THE TWO LEVELS - Tsonev, Ivan; Kazakov, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper an algorithm for communication of communication nodes in LAN with star topology. Probability expressions for the correct sending of messages among the subscribers in the network and the mathematics expectation of the time for the finishing of one cycle from the structure are brought out.